Tradisi Lalaran Sebagai Upaya Memotivasi Hafalan Santri di Pondok Pesantren Putri Al-Mahrusiyah III Mojoroto Kediri Jawa Timur - Erlin Nurul Hidayah; Suko Susilo (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2020)
This paper aims to examine the development of memorization of students who are traversed by way of the tradition of lalaran events that have occurred at the boarding school Al-Mahrusiyah III Ngampel Barat. Here the students have memorization containing the verses of Nadhom in the form of poetry from the Science of Nahwu (Arabic Grammatics) being studied. The students are required to memorize the Nadhom according to their class level. Then memorize the memorized in a deposit to the Mustahiqnya each at the time that has been determined mustahiq or mutually agreed. But in fact, there are still some students who are not fluent, have not been targeted (complete) on the boundaries that have been determined, and even some still difficult to recite the verses Nadhom poetry. In this case the activity of the tradition as an effort to motivate the memorization of students should be really noticed. The research used is qualitative because of the data obtained in the form of words, images or figures. The type of research that researchers use is descriptive that attempts to decrypt existing data. Meanwhile, in the data collection, the author conducted an interview with Mustahiq, the caretaker of the ceremony of Madrasah Diniyah and the student Madrasah Diniyah Al-Mahrusiyah III. Observations to the researcher's location, as well as documentation and subsequent conclusion. The results of the research, namely: (1) The event of the tradition that occurred in Pondok Pesantren Al-Mahrusiyah III experienced differences and changes in this year. This is due to several factors. Among them: There are several students that have not been completed or not yet target in the limits of memorization nadhom that have been determined by each class. Then the factors are derived from the environment and teachers (external) and internal factors (self). (2) Memorization affects urgent (essential) once to study in MADIN. Because of the things that are in MADIN it is behind the dam determined by memorization.